STRATEGI PEMENANGAN POLITIK PDI PERJUANGAN DALAM PILKADA KLATEN 2020: ANALISIS MARKETING POLITIK - Dimas Septian Adi Perdana; Turtiantoro - -; Puji - Astuti (Journal of Politic and Government Studies, 2021)
This research explains the political winning strategy of PDI Perjuangan Klaten, to make Sri Mulyani, their candidate wins the 2020’s Klaten Regional Election.This research aim is to explains, to describe and to analyze the political winning strategy of PDI Perjuangan Klaten. To analyze their strategy, the researcher uses the perspective of political marketing in general, not as rigit as it means, because of the differences between political and economical process. So that the political winning strategy could be identified using marketing perspective without eliminating it’s political process. This research uses the qualitative method with descriptive type of research. This research site located in DPC (Regional Party Administrators) PDI Perjuangan Klaten in which using the purposive sampling technique to determine the informants. This research also uses two sources of data, primary data source and secondary data source obtained by using two forms of data collection technique, which is in-depth interviews and documents review. This research finds that the political winning strategy of PDI Perjuangan Klaten in the 2020’s Klaten Regional Election, divided into two phases, planning phase and implementation phase. The planning phase, divide into three phases such as candidate appointment, establishment of winning political posts and team and candidate SWOT analysis. The implementation phase, the program strategy, figure highlights and political campaign strategy were used as their political winning strategies. Through political marketing perspective, the analysis shows that their political winning strategy were effective but not efficient to be used in the 2020’s Klaten Regional Electionsts.